Improving student satisfaction through total quality management. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2015)
In the higher education blueprint 2013-2025, the Malaysian government outlines a vision for transforming the country’s higher education sector by focusing on system improvements on access, equity and quality of education. The overall arching goal is to produce graduates with 21st century skills through a sustainable education system that meets high international quality standards.